2002
DOI: 10.1161/01.atv.0000030997.02059.bb
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Diet and Statin on NO Bioactivity and Matrix Metalloproteinases in Hypercholesterolemic Patients With Coronary Artery Disease

Abstract: Objective-We investigated the effects of statin compared with the American Heart Association (AHA) Step I Diet on lipoproteins, vasomotor function, tumor necrosis factor (TNF)-␣, and serological markers of plaque stability. Furthermore, we investigated the mechanism of regulation suggested by experimental studies. Methods and Results-For 14 weeks, we administered AHA dietϩplacebo and AHA dietϩsimvastatin (20 mg daily) to 31 and 32 randomly selected patients with coronary artery disease, respectively. Compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
3
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 34 publications
8
55
3
4
Order By: Relevance
“…We and others reported that simvastatin lowers CRP in hyperlipidemic coronary patients (27,28). In the current study, we observed that simvastatin tended to lower CRP in hyperlipidemic patients.…”
Section: Effects On Lipidssupporting
confidence: 70%
“…We and others reported that simvastatin lowers CRP in hyperlipidemic coronary patients (27,28). In the current study, we observed that simvastatin tended to lower CRP in hyperlipidemic patients.…”
Section: Effects On Lipidssupporting
confidence: 70%
“…We calculated that 30 subjects would provide 80% power for detecting a difference of absolute increase, Ն2.1% flow-mediated dilation of the brachial artery between baseline and simvastatin, with ␣ϭ0.05 based on our previous studies. 7,20 The comparison of endothelium-dependent dilation among the 3 treatment schemes was prospectively designated as the primary end point of the study. All other comparisons were considered secondary.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,18,20 Measurements were performed by 2 independent investigators (S.H.H. and W.-J.C.) blinded to the subject's identity and medication status.…”
Section: Vascular Studiesmentioning
confidence: 99%
“…4,7,21,22 C-reactive protein (CRP) levels were determined with an immunonephelometry system according to methods described by the manufacturer (rate nephelometry; Immage, Beckman Coulter) as previously described. 23,24 …”
Section: Laboratory Assaysmentioning
confidence: 99%